2n-dimensional at Fujii model instanton-like solutions and coupling constant’s role between instantons with higher derivatives - Keçeci, Mehmet (My University, 2011)
An instanton-like solution is considered for a class of two-dimensional conformal model with Liouville term. The model expressed here is a new higher-dimensional model with scalar-spinor interaction on evendimensional spaces, and is a generalization of the even-dimensional Fujii model. A recurrence relation for the Fujii model and coupling constant’s indices between relations with interaction constant is extracted. The behavior of G¨ursey, Akdeniz-Smailagi´c and Fujii coupling constants in 4-dimensional conformal models are examined.
Keywords: Instanton; Fujii’s Model; Liouville Term; Conformal Field Theory; Coupling Constant; Scalarspinor Interaction; Even-Dimensional Spaces; Two-Dimensional Conformal Model; Gürsey Term; Scalar-Spinor Interaction